Global Economic Prospects and the Developing Countries 1996 - World Bank (Washington, DC: World Bank, 2019)
This year's report starts from the observation that the participation of developing countries in the accelerated pace of integration over the past decade has been marked by large disparities. While some developing countries have rapidly expanded their engagements in world trade and capital markets, many others have not. Some have even become less integrated with the global economy. Globalization and its impact on developing countries raises policy and research issues that researchers are now beginning to understand more clearly.